A coordination controller in variable speed pumped storage plant. Issue 1 (June 2021) - Zhao, Zhigao; Ma, Weichao; Yang, Jiandong; Yang, Weijia; Huang, Yifan; Wang, Xuewu; Peng, Yumin
Abstract: With the integration of increased variable renewable energy generation, much attention has been devoted on the development of pumped storage. The variable speed pumped storage technology has become a research focus due to its wide operating range, high production efficiency and strong power regulation ability. Moreover, the coordination controller is the key component of variable speed pumped storage plant (VSPSP), it can coordinate the joint operation of governor and converter. The coordinated controller is studied in this work. Aiming at the coordinated control between governor and converter, the novel adaptive strategy of maximum efficiency point tracking is proposed. First, the optimal efficiency curves are described based on model experiment; and then the optimal operating curves of variable speed unit in the operation region is presented based on the BP neural networks; the convergence analysis of mean square error and regression analysis are applied to verify the reliability of results. Aiming at the application of adaptive strategy in the coordination controller, and ensuring the real-time performance, a new effective digital interpolation method is put forward, using programmable logic controller. The signal flows of the control system in variable speed unit are clarified. The proposed adaptive strategy could be easily applied in engineering, providing a technical means for the efficient and flexible operation of VSPSP.